Anti-glomerular basement membrane (Goodpasture) disease exacerbated by invasive pulmonary aspergillosis. Issue 4 (1st October 2020) - Willauer, Alexandra N.; Prakash, Bharat; Saluja, Paramveer; Schuller, Dan
Abstract: Prior reports have associated the unusual presentations of anti-glomerular basement membrane (anti-GBM) disease and pulmonary aspergillosis in an immunocompetent host. We present the case of a previously healthy 24-year-old man who presented with symptoms of hemoptysis, cough, and dyspnea. His environmental risk factors included tobacco use (smoking), hydrocarbon exposure, and an unidentified mold present in his home. Laboratory evaluation revealed positive serum anti-GBM autoantibodies and positive detection of galactomannan in the bronchoalveolar lavage fluid. The diagnosis of anti-GBM disease was confirmed with a kidney biopsy. Management included therapy with voriconazole for aspergillosis and prednisone, plasmapheresis, and eventually cyclophosphamide for anti-GBM disease.